Interceptive Orthodontics with Resin Turbos for Pseudo-Class III Malocclusions - Neal D. Kravitz (Hindawi Limited, 2019)
Background and Overview. Lingual eruption of the permanent maxillary central incisors in the early mixed dentition can result in a traumatic anterior crossbite, causing mobility and gingival recession to the opposing mandibular incisors. Case Description. This case report presents a common finding of a 7-year-old boy with a dental crossbite and pseudo-Class III malocclusion caused by lingual eruption of the maxillary central incisors. An interceptive phase of orthodontic treatment was provided by bonding a beveled resin turbo on the mandibular incisors. The crossbite was corrected in 3 months without any orthodontic appliances. In the absence of the traumatic occlusion, the mandibular incisors stabilized and the gingival tissue was expected to regenerate. Conclusions and Practical Implications. Dentists and orthodontists can place beveled resin turbos on the mandibular incisors to jump an anterior dental crossbite conservatively, without the use of orthodontic brackets and wires.